The Confiscation of Husbands’ Wealth as A Collateral for Post-Divorce Child Support: Perspective of Maqāṣid Al-Sharī'ah - Zuhdi, Syaifuddin; Dimyati, Khudzaifah; Wardiono, Kelik; Shofia, Rahma; Hakim, Abdul (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
A husband is obliged to take care of his family, including his wife and children. when they divorce, he doesn’t have to support his wife anymore, but he still has to support their children. With the compilation of Islamic Law, statute no 1 of 1974 and circular letter of Supreme Court, Courts decide how much the father needs to pay for child support after a divorce through judge’s consideration. But sometime, fathers don’t follow this decision. In Indonesia, a 2021 circular letter from the Supreme Court allows the court to take the husband's property to ensure the children get the support they need after the divorce. This research aims to determine the concept of confiscation of husband's property as a guarantee for child support after divorce from a maqāṣid al-sharī'ah perspective. The method used in this research is a normative juridical method which is descriptive. Data was collected through in-depth interviews and religious court studies. The research results show that the concept of including the ex-husband's assets as collateral for post-divorce child support is included in the execution submitted to the Religious Court for the father's husband's negligence in implementing the provisions regarding child consent in the divorce decision. This process can be submitted by the ex-wife or child's mother or child's guardian to the Religious Court. The concept of confiscating the husband's property as a guarantee for children's support after divorce can provide benefits for children in the form of hifdz nafs (protecting themselves) and hifdz aql(protecting reason), as well as benefits for fathers in the form of hifdz nafs (protecting offspring) and hifdz maal(protecting assets).